Evaluation of Short and Long Term Cold Stress Challenge of Nerve Grow Factor, Brain-Derived Neurotrophic Factor, Osteocalcin and Oxytocin mRNA Expression in BAT, Brain, Bone and Reproductive Tissue of Male Mice Using Real-Time PCR and Linear Correlation Analysis - Camerino, Claudia; Conte, Elena; Caloiero, Roberta; Fonzino, Adriano; Carratù, Mariarosaria; Lograno, Marcello D.; Tricarico, Domenico (Frontiers in Physiology, 2018)
The correlation between the Ngf/p75ntr-Ntrk1 and Bdnf, Osteocalcin-Ost/Gprc6a and Oxytocin-Oxt/Oxtr genes, was challenged investigating their mRNA levels in 3 months-old mice after cold-stress (CS). Uncoupling protein-1 (Ucp-1) was used as positive control. Control mice were maintained at room temperature T=25°C, CS mice were maintained at T=4°C for 6h and 5-days (N=15 mice). RT-PCR experiments showed that Ucp-1 and Ngf genes were up-regulated after 6h CS in brown adipose tissues (BAT), respectively, by 2 and 1.5-folds; Ucp-1 was upregulated also after 5-days, while Ngfr (p75ntr) and Ntrk1 genes were downregulated after 6h and 5-days CS in BAT. NGF and P75NTR were upregulated in bone and testis following 5-days, and P75NTR in testis after 6h CS. Bdnf was instead up-regulated in bone following 5-days CS and down-regulated in testis. OST was upregulated by 16 and 3-fold in bone and BAT, respectively, following 5-days CS. Gprc6a was upregulated after 6h in brain, while Bglap (Ost) gene was downregulated. Oxt gene was upregulated by 5-fold following 5-days CS in bone. Oxtr was upregulated by 0.5 and 0.3-fold, respectively, following 6h and 5-days CS in brain. Oxtr and Oxt were downregulated in testis and in BAT. The changes in the expression levels of control genes vs genes following 6h and 5-days CS were correlated in all tissues, but not in BAT. Correlation in BAT was improved eliminating Ngfr (p75ntr) data. The correlation in brain was lost eliminating Oxtr data. In sum, Ucp-1 potentiation in BAT after cold stress is associated with early Ngf-response in the same tissue and trophic action in bone and testis. In contrast, BDNF exerts bone and neuroprotective effects. Similarly to Ucp-1, Bglap (Ost) signaling is enhanced in bone and BAT while it may exert local neuroprotective effects thought its receptor. Ngfr (p75ntr) regulates the adaptation to CS through a feed-back loop in BAT. Oxtr regulates the gene-response to CS through a feed-forward loop in brain. Overall these results expand the understanding of the physiology of these molecules under metabolic thermogenesis.